Hipóteses de desconsideração do laudo pericial pelo juiz no código de processo civil - Pereira, Julia Weygand Siqueira (2023)
The Brazilian civil procedure is carried out by the evidence produced in the records, that these are the procedural instruments with the greatest capacity to undermine and influence the judgment on the merits. Minority shares are those that do not depend on the instruction or based solely on documentary evidence. In particular, among evidence, expert evidence stands out, as this has as its essence the transcendence of the merely legal discussion, integrating areas into the civil procedure of knowledge of which the judge, theoretically, is unaware. Due to this ignorance, the magistrate, in actions that require the production of expert evidence, relies on the figure of the expert to express his decision, behold, he acts as an auxiliary to the judgment, clarifying technical-scientific issues involving the cause. However, this assistance provided by the expert, materialized in the expert report, has object of fearful judicial control, since it has been observed in case law unrestricted adherence to the fundamentals and results of the expertise, without the magistrate effectively focuses on the evidence produced. This has been leading generic decisions, directly violating the duty to state reasons for decisions judicial